Intensity of The Use of Gadgets to Attention Deficit Disorder in Children - Menik Sri Daryanti; Enny Fitriahadi (Jurnal Kebidanan, 2022)
The demands of the times and the many benefits of gadgets make many parents start introducing gadgets from an early age. The use of gadgets can have an impact on children, be it a negative impact or a positive impact. The negative impact felt by children in terms of motor, accepting learning and difficulties in socializing with other people. Attention disorder is one of the main psychiatric problems that is often found in children under 7 years of age. In some people, they still cannot recognize this disorder even though this disorder can be found in everyday life, both in preschool children, adolescents, and even adults. The purpose of this study was to determine the effect of the intensity of the use of gadgets on disruption of concentration of attention in elementary school children. This type of research is a quantitative study with a correlational analytic design and a cross sectional approach. Respondents taken in this study were students in elementary schools in the Sleman Regency in the age range 7-10 years and their mothers using the quota sampling technique. Data analysis using chi square. Based on the results of the calculation of the chi square test, it is known that the p value is 0.000 so that it can be concluded that the p value is 0.000 <0.05. From the results of the bivariate analysis, it can be concluded that there is an effect of the intensity of the gadget on attention disruption in school-age children. It is hoped that parents and teachers can monitor the intensity of the use of gadgets in children.